Antioxidant Activity Test of Langsat (Lansium domesticum) Bark Extract with DPPH - Nur, Amran; Saleh, Rahmat Dian; Rahman, Ismail; Fiskia, Ermalyanti; Rahman, Safriani (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
Background: The langsat plant is a traditional plant that has long been used as an alternative to treat various health problems. Langsat bark apparently has extraordinary benefits and is closely related to its ability to fight free radicals. The bad effects caused by free radicals on the body can be prevented by using a substance called an antioxidant. The benefits of antioxidants for the body include protecting body cells from damage caused by free radicals. Langsat bark has extraordinary benefits, one of which is that it contains compounds that are antioxidant, anti-inflammatory, anti-diabetic and anti-cancer. Where langsat bark is known to contain several secondary metabolites, namely alkaloids, flavonoids, saponins, tannins and triterpenoids. Objective: This study aims to determine the antioxidant activity of langsat (Lansium domesticum) bark extract. Method: Determination of antioxidant activity using the DPPH (2,2-diphenyl-1-picrihidrazyl) method. Results: The antioxidant value of vitamin C and langsat bark extract are included in the very strong antioxidant category because both have IC50 values 50 ppm. Where the IC50 value 50 ppm is classified as a very strong antioxidant. In testing vitamin C, an average IC50 value of 6,378 μg/mL was obtained, while for langsat bark extract an average IC50 value was 10,654 μg/mL.Conclusion: Langsat bark extract has an IC50 value of 10,654 μg/mL so it is categorized as a very strong antioxidant.